1999
DOI: 10.1590/s0102-76381999000300010
|View full text |Cite
|
Sign up to set email alerts
|

Uso de corticóide como inibidor da resposta inflamatória sistêmica induzida pela circulação extracorpórea

Abstract: RESUMO: A circulação extracorpórea (CEC) propicia o desenvolvimento de uma Síndrome de Resposta Inflamatória Sistêmica, com liberação de citocinas responsáveis por várias manifestações clínicas. Objetivo: Observar a liberação das citocinas Fator de Necrose Tumoral Alfa (TNFα) e Interleucina 6 (IL-6) e verificar as alterações clínicas produzidas em pacientes submetidos à revascularização do miocárdio com CEC, utilizando ou não corticóide. Casuística e Métodos: Foram estudados 30 pacientes, sendo 15 (Grupo I) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 70 publications
0
14
0
9
Order By: Relevance
“…Brasil et al [31] have showed similar results with corticosteroid administration with less proinflammatory cytokines release in patients underwent bypass. The TNFá has evident release decrease and less adverse systemic effects resulting from inflammatory response after bypass.…”
Section: Discussionmentioning
confidence: 70%
“…Brasil et al [31] have showed similar results with corticosteroid administration with less proinflammatory cytokines release in patients underwent bypass. The TNFá has evident release decrease and less adverse systemic effects resulting from inflammatory response after bypass.…”
Section: Discussionmentioning
confidence: 70%
“…Movements arise in the membrane, directed to the contact receptors, so that adhesion, migration and phagocytosis take place. Finally, the synthesis of enzymes that are useful for antimicrobial activities occurs, enabling the activation of the macrophage (BRASIL et al, 1999). Their key triggering mediators are pro-inflammatory cytokines -interleukins (1,2,6,8,12), interferons and necrosis factors -lipopolisaccharides (LPS) and colony-stimulating factors (CSFs) -responsible for the recruitment of neutrophils to the site of infection and for cleaning bacterial infection.…”
Section: Macrophage In Sepsismentioning
confidence: 99%
“…As a result, there is an important increase in cytokines, what may lead to major consequences, like vascular damage and organ failure, which are severe outcomes that usually affects the septic patient. The main inflammatory mediators released are adhesion molecules (selectin, integrin and immunoglobulin); nitric oxide (NO); the metabolic products of arachidonic acid, like thromboxane A2, prostaglandins and leukotrienes; and the platelet activating factor (PAF) (BRASIL et al, 1999). However, due to their permanence in a hyperenriched environment, macrophages become irresponsive to toxins-a phenomenon called tolerance to endotoxins-responding with macrophage activation type M2.…”
Section: Macrophage In Sepsismentioning
confidence: 99%
“…Ohri et al [16] have shown that changes in thyroid hormone levels are likely to detect the immediate postoperative period, since at this stage, there is an active state of catabolism associated with high rates of oxygen consumption [17][18][19][20]. Some authors have postulated that the decrease in thyroid hormones in the post-CPB favors the occurrence of global myocardial dysfunction and arrhythmias, especially atrial fibrillation [21][22][23][24][25].…”
Section: Fig 3 -Comparison Between Two Moments For Total T3 Free T3mentioning
confidence: 99%